Study on Point Contact Parabolic Tooth Surface Construction and Sliding Coefficient Calculation Method based on Selectable Contact Trail - Shuai Peng; Jing Zhang; Linxiang Wang (Jixie chuandong)
A new type of point contact gear pair is proposed. Based on a tooth surface，the flexible contact trail is selected according to the design requirements，and the meshing pair gear is constructed，and the sliding coefficient calculation method of the new gear pair is deduced. Taking the involute internal gear as the given gear and the parabolic gear as the matching gear，an internal gear pair is designed. The results show that during the whole meshing process，the gear pair keeps point contact state at all times，and the meshing point moves along the theoretical contact trail，which is consistent with the theoretical analysis. The variation range of the sliding coefficient mainly depends on the involute parameter values corresponding to the entry and exit points selected at both ends of the gear.